Recurrent bleeding during standard anticoagulant therapy in comorbid patients with atrial fibrillation: a clinical case report - A. A. Kudriavtseva; E. V. Kolpachkova; Z. A. Gebekova; T. A. Sadulaeva; A. A. Sokolova; D. A. Napalkov (Рациональная фармакотерапия в кардиологии)
The question of the safety of direct oral anticoagulants (DOACs), despite their high efficacy in the prevention of thrombotic events in atrial fibrillation (AF), remains relevant due to the risk of developing hemorrhagic events while taking standard doses, which requires a thorough personalized approach. The article presents a clinical case of the development of spontaneous hematomas on the skin of the upper and lower extremities and hemarthrosis of the knee joint while taking 20 mg of rivaroxaban in a 72-year-old patient with AF without impaired renal and hepatic function. Due to the increase in the residual plasma concentration of rivaroxaban, a pharmacogenetic study and the Thrombodynamics (TD) test were performed. A pharmacogenetic study did not reveal significant gene polymorphisms associated with the metabolism of rivaroxaban. However, TD allowed us to confirm the presence of significant hypocoagulation at the peak of the residual blood concentration of the drug in the blood, which could cause recurrent hemorrhagic events in the patient. In addition, the patient is taking amiodarone at a dosage of 200 mg per day, which does not allow us to rule out drug-drug interaction, despite the inconsistency of the literature data.